Rate and correlates of self-stigma in adult patients with early psychosis - Chu, Ryan Sai Ting; Ng, Chung Mun; Chu, Sheung Chit; Lui, Tsz Ting; Lau, Fu Chun; Chan, Sherry Kit Wa; Lee, Edwin Ho Ming; Hui, Christy Lai Ming; Chen, Eric Yu Hai; Lui, Simon Sai Yu; Chang, Wing Chung (Frontiers in Psychiatry, 2023)
Introduction: Self-stigma impedes recovery process and is associated with poorer clinical and functional outcomes in people with psychotic disorders. However, there is limited research specifically examining self-stigma in the early stage of illness, and mixed findings were observed regarding factors associated with increased self-stigma. We aimed to investigate the rate and correlates of self-stigma in a cohort of adult patients with early psychosis using a comprehensive array of clinical, treatment and other illnessrelated variables. Methods: A total of 101 Chinese adult early psychosis patients aged 26-55 years who had received threeyear psychiatric treatment for first psychotic episode in Hong Kong and completed self-stigma assessment were included for the current investigation. A broad range of assessments encompassing socio-demographics, premorbid adjustment, onset and illness profiles, symptom severity, psychosocial functioning, treatment characteristics and medication side-effects were conducted. Results: Twenty-eight (27.7%) patients had moderate-to-high levels of self-stigma. Univariate linear regression analyses showed that age at study entry, sex, educational level, age at psychosis onset, duration of untreated psychosis (DUP), insight level, global psychosocial functioning, and the use of secondgeneration antipsychotic were related to self-stigma levels. Final multivariable regression model revealed that female sex, younger age at entry, longer DUP and better insight were independently associated with higher levels of self-stigma. Conclusion: More than one-fourth of early psychosis patients experienced significant self-stigma, highlighting an unmet need for early detection and intervention of self-stigma in the initial years of illness. Further investigation is warranted to clarify trajectories and predictors of self-stigma in the early illness course.